Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1039/d2tc05390j
|View full text |Cite|
|
Sign up to set email alerts
|

Heads or tails: investigating the effects of amphiphile features on the distortion of chiral nematic liquid crystal droplets

Abstract: Liquid crystal-based sensing has fast become a growing field, harnessing the sensitivity of liquid crystals to their surroundings to provide information about the analytes present, including surface-active amphiphiles such as...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…In NLC droplets, we can neglect the T terms in Equations 1 and 2, so we need only look at the difference between the splay and bend conformations. In contrast, previous work has shown that chiral nematics in general do show a greater sensitivity to confinement-and surface-driven effects [66,67], and we also cannot neglect the T terms; in fact, T tan 6 = T nor ,a n dp a r t i c u l a r l yu p o nt h ea d s o r p t i o no f amphiphiles [27]. The consequence of this is likely that the energy barrier to switch between the two configurations in the chiral nematic (with the normally aligned system being lower energy) is much lower than for the nematic, making the CLC more susceptible to a change of alignment.…”
Section: Chiral Versus Non-chiral Nematic Liquid Crystals Show An Anc...mentioning
confidence: 81%
See 3 more Smart Citations
“…In NLC droplets, we can neglect the T terms in Equations 1 and 2, so we need only look at the difference between the splay and bend conformations. In contrast, previous work has shown that chiral nematics in general do show a greater sensitivity to confinement-and surface-driven effects [66,67], and we also cannot neglect the T terms; in fact, T tan 6 = T nor ,a n dp a r t i c u l a r l yu p o nt h ea d s o r p t i o no f amphiphiles [27]. The consequence of this is likely that the energy barrier to switch between the two configurations in the chiral nematic (with the normally aligned system being lower energy) is much lower than for the nematic, making the CLC more susceptible to a change of alignment.…”
Section: Chiral Versus Non-chiral Nematic Liquid Crystals Show An Anc...mentioning
confidence: 81%
“…However, this would require a different platform or a different added stabilizer to enable the CLC to optimally function as a sensor. Since the CLC is directly switched by the oleosins and we have shown in previous work that we can differentiate between different amphiphiles using a color channel analysis [26,27], further investigation could establish if we can differentiate between proteins with different lengths of amphipathic helices and hydrophilic "wings", an important aspect of being able to identify their biological role in cells.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…[ 5,7,15,16,20 ] Increasing attention has been paid to sensing with chiral nematic liquid crystals (CLCs), which can exhibit brilliant structural color reflection [ 21–24 ] that can additionally provide information about the stimuli causing the change, whether it be temperature, [ 10,12,13 ] strains, [ 8,25 ] or adsorption of amphiphiles. [ 23,26–28 ]…”
Section: Introductionmentioning
confidence: 99%